Communication in the Family - Olteanu, Cecilia Mihaela (New Trends in Psychology, 2023)
The mission of communication, we can agree, is obvious, however, the simple possession of language is insufficient for talking with another person. For effective communication, language and social skills are mutually oriented. Here, the family has a defining role of regulation and training. The new school requirements diversify the affective register; thus the feeling of duty appears, its formation requires direct guidance from the adult and finally the crystallization of a balanced work regime. One of the essential results of the affective relations between the child and his parents, or the adults who play their role, is the birth of moral feelings specific to the duty of conscience. In this part of childhood, bonds with parents are created specifically for protection, support and reassurance. The role of the family must be to provide a warm welcoming secure shelter or in other words a home, which is regulated by simple but clear rules. Shared attention and communication in the family is very important, especially in the early stages of children’s language development.